Aggregation-induced emission of active nanoparticles based on konjac glucomannan: Fabrication, properties, and applications. (14th June 2022) - Guan, Lianxiong; Zeng, Zhi; Zhao, Rui; Hu, Sheng; Liu, Wei; Tian, Dating
Abstract: Recently, the design of aggregation-induced emission (AIE) materials with good water-solubility and biocompatibility has attracted much attention. In this work, amphiphilic AIE-active nanoparticles (KGM-TPE) were synthesized by a facile Schiff base condensation of oxidized konjac glucomannan with amino-tetraphenylethylene. The final KGM-TPE had good water dispersibility and could self-assemble into nanoparticles with average diameters ranging from 100 to 200 nm. A cytotoxicity test showed that the cell survival was approximately 90% even when the concentration of KGM-TPE reached 150 μg/mL, indicating that KGM-TPE possessed good biocompatibility. In addition, the excellent cell imaging and good anti-counterfeiting function results of KGM-TPE indicated that this material has great potential in the fields of biomedicine and anti-counterfeiting. Graphical abstract: Image 1 Highlights: KGM-TPE, a novel AIE-active nanoparticle, was prepared via a facile Schiff base reaction. KGM-TPE showed good biocompatibility, water dispersibility, and AIE properties. KGM-TPE had excellent potential in the fields of biomedicine and anti-counterfeiting.